2020
DOI: 10.17652/rpot/2020.2.18204
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of discrimination and inclusion of brazilian transgender people in the labor market

Abstract: Transgender women and men continue to encounter barriers, motivated by discrimination, in their daily lives and-although much less studied-in achieving a satisfactory career. The objective of this study is to describe transgender women's and men's labor market discrimination. A cross-sectional study was performed using data from 384 participants who identified as having a gender different than the one assigned at birth. Regarding their current work situations, 33.85% of transgender women and 45.16% of transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…The original project sought to improve the quality of life of transgender people in Ontario, Canada, by measuring levels of social exclusion and its impact on physical and mental health. Studies derived from the “Trans health” project include the impact of minority stress on suicide ideation, suicide attempts and depressive symptoms [ 30 ]; prevalence of labor market discrimination [ 32 ]; an assessment of transgender-specific healthcare needs in the Brazilian context [ 35 ]; HIV-related healthcare needs [ 36 ]; the impact of family support on the process of gender affirmation [ 37 ]; and the association between parental participation in transgender children’s life and discrimination experiences [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original project sought to improve the quality of life of transgender people in Ontario, Canada, by measuring levels of social exclusion and its impact on physical and mental health. Studies derived from the “Trans health” project include the impact of minority stress on suicide ideation, suicide attempts and depressive symptoms [ 30 ]; prevalence of labor market discrimination [ 32 ]; an assessment of transgender-specific healthcare needs in the Brazilian context [ 35 ]; HIV-related healthcare needs [ 36 ]; the impact of family support on the process of gender affirmation [ 37 ]; and the association between parental participation in transgender children’s life and discrimination experiences [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The murder rates in this population in Brazil are considered to be the highest in the world, with an average of 118.2 murders/year between 2008 and 2019 [ 31 ]. Between 33.85% and 45.16% of these individuals are not currently employed, most of them reporting having jobs denied due to their gender identity [ 32 ]. A study on the health conditions of TW in the state of Rio de Janeiro found that the participants had low income (62.0% lived on less than USD10.00/day), demonstrated a very high involvement in sex work (78.6%) and reported a higher occurrence of sexual (46.3%) and physical (54.0%) violence [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Houve também baixa participação de pessoas transgêneros e travestis, situação semelhante às pesquisas anteriores na área (Resnick & Galupo, 2019;Richard, 2021). O mercado de trabalho é particularmente mais difícil para esta parcela da população, que apresenta as maiores taxas de desemprego e tende a ser direcionada a trabalhos informais e autônomos (Costa et al, 2020), o que pode refletir em sua baixa participação nas pesquisas.…”
Section: Discussionunclassified
“…Todavia, elas podem impactar em sua inserção e permanência no mercado de trabalho, aliadas à negligência de direitos básicos e a vulnerabilidade social. A pessoas transgênero enfrentam ainda mais dificuldades, como altas taxas de desemprego, subemprego e insatisfação no trabalho, além de serem direcionadas a trabalhos informais, autônomos e prostituição (Costa et al, 2020).…”
unclassified